Listrik / Chris Woodford ; alih bahasa, Yosephine Ratih Ismayanti ; penyunting, Rudiyanto, B. Waluyo - WOODFORD, Chris; Ismayanti, Yosephine Ratih; Rudiyanto; Waluyo, B (Pakar Raya, 2006)
40 hlm ilus 25 cm